Implementation of Law No. 2 of 1960 concerning the Implementation of Profit Sharing in Putat Village, Tanggulangin District, Sidoarjo Regency - Rifqi Ayzudin (Universitas Muhammadiyah Sidoarjo, 2022)
In its development, the production sharing agreement was then regulated by Law Number 2 of 1960 concerning Production Sharing agreements that were born based on customary law in Indonesia. The problem in this paper is how the implementation of Law Number 2 of 1960 Concerning Land Sharing Agreements in Putat Village, Tanggulangin District, Sidoarjo Regency and What is the profit sharing concept in Law No. 2 of 1960 gave the possibility for the application of custom mechanisms in Putat Village. This thesis uses an empirical juridical approach, primary data obtained through data collection in the field which is then supplemented with literature studies for later qualitative analysis. The implementation of Law Number 2 of 1960 concerning Agricultural Land Production Sharing Agreements in Putat Village, Tanggulangin District, Sidoarjo Regency has not been fully effective. The community tends to choose to implement it verbally. The inhibiting factor for the adoption of Law Number 2 of 1960 concerning Agricultural Land Product Sharing Agreements in Putat Village, Tanggulangin Subdistrict, Sidoarjo Regency is that most of the people are not aware of the provisions of the Agricultural Product Sharing Agreement stipulated in the Law This is due to the absence of socialization from village officials and related offices, lack of insight from the community due to low levels of education, the existence of bad habits from the community that underestimate any regulations related to agriculture.